Moderasi Beragama dalam Tradisi Nyadran Gunung Silurah (WBTB 2024): Analisis Kontekstual dan Kontribusi Sosial-Keagamaan - Muhamad Masrur; Dwi Tika Wulan Sari; Fika Dealova; Nafal Fikri; Fatisa Dina Rahmadayanti (Moderasi : Journal of Islamic Studies, 2025)
This study discusses public acceptance of the Nyadran Gunung Silurah tradition in Batang Regency after its designation as an Intangible Cultural Heritage (WBTb) of Indonesia in 2024 in the context of strengthening religious moderation. The objectives of this study are to describe the implementation of Nyadran, analyze the forms of community acceptance, and identify the values of religious moderation contained therein. This study uses a qualitative approach with a literature study method through a search of academic literature from relevant articles and studies. The data were analyzed descriptively using content analysis techniques to find themes of religious, social, and cultural values in the Nyadran tradition. The results showed that the Silurah community had a high level of acceptance of this tradition as a form of harmony between religion and culture. Values of moderation such as tasamuh (tolerance), tawazun (balance), i'tidal (justice), and syura (deliberation) are internalized in every ritual procession. The Nyadran Gunung Silurah tradition serves as a medium for cultural preservation, ecological spirituality, and a means of social education that strengthens religious moderation at the local level.